Some Generalizations of Semisimple Gamma Rings - Abbas , Mehdi S.; Al-Saadi, Saad Abdul kadhim; Shallal, Emad Allawi (Iraqi Journal of Science, 2021)
In this paper we introduce and study the concepts of semisimple gamma modules , regular gamma modules and fully idempotent gamma modules as a generalization of semisimple ring. An module is called fully idempotent (semisimple , regular) if for all submodule of (every submodule is a direct summand, for each , there exists and such that . We study some properties and relationships between them.